2012
DOI: 10.1021/ja304239g
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cell Surface Protein Imaging by Extended Self-Assembling Fluorescent Turn-on Nanoprobes

Abstract: Visualization of tumor-specific protein biomarkers on cell membranes has the potential to contribute greatly to basic biological research and therapeutic applications. We recently reported a unique supramolecular strategy for specific protein detection using self-assembling fluorescent nanoprobes consisting of a hydrophilic protein ligand and a hydrophobic BODIPY fluorophore in test tube settings. This method is based on recognition-driven disassembly of the nanoprobes, which induces a clear turn-on fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 47 publications
(31 reference statements)
2
97
0
Order By: Relevance
“…BODIPY dyes are known to self-assemble and self-quench in aqueous solutions3637. To understand how CO fluoresces upon addition of caffeine, we first conducted dynamic light scattering (DLS) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…BODIPY dyes are known to self-assemble and self-quench in aqueous solutions3637. To understand how CO fluoresces upon addition of caffeine, we first conducted dynamic light scattering (DLS) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…86 A Bodipy probe with a folate receptor 39 (Figure 16b) exhibited extremely weak emission in aqueous solution due to aggregation induced quenching. 87 The emission was found to increase gradually upon addition of dihydrofolate reductase indicating the disassembly of nanoparticles (Figure 16c). Thus, the self-assembled nanoparticles of 39 were used as a turn on probe for live cell imaging of cancer cells, which over express foliate receptor.…”
mentioning
confidence: 97%
“…Very recently, it has been demonstrated that such a supramolecular protein imaging method can be applied to intracellular proteins, as well as cell-surface proteins under live cell conditions. 187,188 Fig. 12 Two key strategies to sense proteins of interest using protein-ligand interaction (a) with a ligand tethering an environmental-sensitive probe and (c) with an amphiphilic ligand derivative tethering a hydrophobic probe.…”
Section: Protein Sensing Through Protein-ligand Interactionsmentioning
confidence: 99%